RESULTS OF TRANSARTERIAL CHEMOEMBOLIZATION OF STOMACH CANCER METASTASES IN THE LIVER - D. T. Arybzhanov (Креативная хирургия и онкология)
Results of treatment of 60 patients with gastric  cancer  with liver metastases are analyzed. Immediate results have shown  the effectiveness of treatment after 2 cycles of TACE in 49(81,7%) patients: partial response was observed in 36 (60%) patients and a significant regression of the process  was observed in 13 (21,6%) patients, the process  of stabilization was observed in 11 (18,3%) patients. Subsequent evaluation of the effectiveness of the results of treatment of patients after 4 and 6 courses of TACE were identical. Partial response was observed in the  process  of 18 (30%) patients, stabilization persisted in 12 (20%) patients.  The progression by 8-9  months of  treatment was  seen  in 30  (50%) patients. In assessing the  general  condition of patients focused on the  quality of life for patients. All patients  had  a  positive  treatment  outcome  overall  by  Karnovsky  remained  at  the  level  of 75-80% (ECOG 1-2), which does not limit the patients and did not require prolonged hospitalization. The average time of hospitalization of patients with each course  (cycle) TACE averaged 5±2  day. In the dynamic tracking  of patients in terms  of 12, 18, 24 months more than 12 months 24 (40%) patients are alive, 11 (18,3%) patients are alive during 18 months.  8 (13,3%) patients are alive during 24 months. Median survival was 15,5±1,2 months. Thus, in the present the TACE method in stomach cancer metastasis treatment can be considered like an effective, low toxicity method of  treatment and  may be a method of choice for improving survival and quality of life of the difficult category of patients.